Perspektif Siyasah Syari'ah terhadap Ketidakstabilan Regulasi dan Kepercayaan Investor Global: Studi Kasus Relokasi Tekno-Industri di Asia Tenggara - bobby ferly; Nurus Shalihin Nurus; Ikhwan Matondang Ikhwan; Muchlis Bahar Muchlis Bahar; Elfia Elfia (Al-Mutharahah: Jurnal Penelitian dan Kajian Sosial Keagamaan, 2026)
This study analyzes the impact of regulatory instability on global investor trust from the perspective of Siyasah Syari'ah, with a focus on techno-industrial investment relocation in Southeast Asia during 2024–2025. Using a qualitative normative-juridical method with a comparative case study approach, this research examines three pivotal cases: Apple's iPhone 16 ban in Indonesia, Tesla's Gigafactory cancellation, and NVIDIA's expansion into Vietnam. The study applies three core Siyasah Syari'ah concepts Gharar Siyasi (political uncertainty), Hifz al-Mal (protection of wealth), and Maslahah Mursalah (public interest) as analytical lenses to evaluate government investment policies. Findings reveal that Indonesia's erratic protectionist approach, including sudden product bans and an oversized bureaucracy, constitutes Gharar Siyasi, thereby undermining investor confidence and causing capital flight to Vietnam, which demonstrably applied the principle of Maslahah through incentive-based policies (Decree 182/2024). The study concludes that legal certainty is both a rational economic requirement and a moral-religious obligation in Islamic governance. Policy recommendations are offered for Indonesia to reform its regulatory approach toward a more transparent, incentive-oriented, and Shari'ah-compatible investment environment.